A Way to Conserve Cultural Heritage in Architecture Creation - Kelkoul, Rahmani Leila (ICONARCH International Congress of Architecture and Planning, 2014)
Using definitions of the type and model and through some architectural works this presentation proposes an approach and a way to preserve the architectural heritage through the architectural creation not by reproducing and copying but considering it as a referential reservoir of ideas and architectural principles.